Integrative Approach to the Management of Diabetic Neuropathy Using Marma Chikitsa and Panchakarma Therapies - V S Charantimath; Bharadwaj; Sreyas Naik; A V Srinivasan (AYUSHDHARA, 2025)
The National Centre for Disease Control (NCDC) has reported that India has 6.51 crore diabetes cases, with projections reaching 10.9 crore by 2035. Diabetic neuropathy is a prevalent complication of long-standing Type 1 and Type 2 Diabetes mellitus, affecting approximately 10.5% to 44.9% of individuals. With Diabetes emerging as a global epidemic in both developed and developing nations, effective management of its complications is the need of the hour. Diabetic neuropathy manifests as nerve damage, leading to symptoms such as hyperesthesia, paresthesia, pain, and sensory loss. Despite advancements in glycemic control strategies, conventional treatment remains inadequate in addressing neuropathic symptoms comprehensively. To bridge this gap, a holistic approach integrating Marma Chikitsa with Panchakarma therapies was implemented at our center, for the management of Diabetic Neuropathy where-in 5 patients presented with symptoms of diabetic neuropathy. This integrative intervention yielded significant improvements, demonstrating the efficacy of Marma Chikitsa in conjunction with Panchakarma therapies. Notably, patients experienced faster and more effective relief, as validated by the Modified Toronto Clinical Neuropathy Score (TCNS) assessment. These findings highlight the potential of Ayurveda-based therapies in enhancing neuropathic symptom management and underscore the necessity of adopting a holistic framework for diabetic care.